2017
DOI: 10.1161/jaha.116.004780
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Prophylactic Dexmedetomidine in Preventing Postoperative Junctional Ectopic Tachycardia After Pediatric Cardiac Surgery

Abstract: BackgroundPostoperative junctional ectopic tachycardia is one of the most serious arrhythmias that occur after pediatric cardiac surgery, difficult to treat and better to be prevented. Our aim was to assess the efficacy of prophylactic dexmedetomidine in preventing junctional ectopic tachycardia after pediatric cardiac surgery.Methods and ResultsA prospective controlled study was carried out on 90 children who underwent elective cardiac surgery for congenital heart diseases. Patients were randomized into 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 25 publications
2
33
0
4
Order By: Relevance
“…Dexmedetomidine is a highly selective α2 adrenoceptor agonist with sedative, analgesic, and anxiolytic properties and is widely used as a sedative and analgesic in the ICU. Currently, several small, single‐center randomized controlled trials (RCTs) reported that prophylactic dexmedetomidine is useful for the prevention of JET in pediatric cardiac surgery patients . Furthermore, the present research also suggested that the administration of dexmedetomidine might reduce the incidence of AKI after cardiac surgery with CPB .…”
Section: Introductionsupporting
confidence: 50%
“…Dexmedetomidine is a highly selective α2 adrenoceptor agonist with sedative, analgesic, and anxiolytic properties and is widely used as a sedative and analgesic in the ICU. Currently, several small, single‐center randomized controlled trials (RCTs) reported that prophylactic dexmedetomidine is useful for the prevention of JET in pediatric cardiac surgery patients . Furthermore, the present research also suggested that the administration of dexmedetomidine might reduce the incidence of AKI after cardiac surgery with CPB .…”
Section: Introductionsupporting
confidence: 50%
“…Two additional secondary outcomes, inotrope scores and total mechanical ventilation time, were reported by 4 studies, which showed significant decreases in both outcomes (Figure B,C). Specifically, there was a decrease in the standard difference in mean of inotropic scores in the dexmedetomidine group by −0.562 (CI 95% −1.087;−0.017, P = .043), and a decrease in the standard difference in mean of total mechanical ventilation time in the dexmedetomidine group by −1.169 hours (CI 95% −2.012;−0.35, P = .007).…”
Section: Resultsmentioning
confidence: 90%
“…Of note, 6 studies reported choice of “placebo” administration in the control group, and they were variable (Table ). Three studies used normal saline infusion . In another study, fentanyl infusion was reported .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations